Solving Household Economic Problems According to the Principles of Eight Preceptsand Sappurisadhamma of Banphou People Phralab District Khonkaen Province - Leeanansaksiri, Aleena; บำรุงภักด โสวิทย์ (Journal of Graduate MCU KhonKaen Campus, 2019)
The aims of this qualitative research were: 1) to study the condition of household economic problems of Ban Phou village, Phralap sub-district, KhonKaen; 2) to integrate the principles of eight precepts and sappurisadhamma to solve such problems of the village. This qualitative research has its tools as 1) in-depth interview form andthe data were collected by interviewing 30 key informantsand 2) participatory observationand analyzed by deductive-methoddescriptive analysis. The research results were found that Ban Phou is a village with a large population living close to KhonKaen Municipality. The majority of the population is agricultural workers. Due to the conditions of the terrain, it causes 4 household economic problems for the population, namely: 1) inadequate revenue; 2) unbalanced expenses in living; 3) debt from borrowing and living according to modern society; 4) problems of saving money in daily life that has more expenses than income. Integration of the principles of eightprecepts and sappurisadhamma in order to solve the economic problems of the villagers of Ban Phou villagers, Khon Kaen can be done in three levels starting with promoting community-driven organizations; the second level is to request the continuous support from monks to be leaders in training the principles of eight precepts and sappurisadhamma for the people of Ban Phou. The third level is to show the role of community leaders in every department by pointing out ways to solve problems, alleviate and promotepotentials through the Eight precepts (uposatha-sīla) andSappurisadhamma (Dhamma, qualities of a good man; virtues of a gentleman) in order for the villagers to have a pattern of living that promotes economic status at the same time. The results of this are: 1) more income 2) expenditure decreases with the pattern 3) awareness of debt disadvantage and 4) more savings and allocation.